KEPEMIMPINAN DALAM ISLAM SERTA PRINSIP-PRINSIP PEMERINTAHAN DALAM AL-QURAN - hemlan elhany (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2019)
Immediately, after the Prophet Muhammad received the revelation he began his prophetic mission. Through a very heavy struggle, for 13 years in Mecca, he only gained followers of no more than 100 people. After migrating to Medina, he gained a lot of sympathy and followers, even able to build a free and independent Islamic community under the leadership of the Prophet. In this city of Medina, in less than two years, he has published a charter which regulates the life and relationships between such diverse communities. The charter is known as the Charter of Medina (Shohifah-Madinah). In the 10-year period the Prophet in Medina had built a (civilized) society, civil society. In this country of Medina, for Muslims, the Prophet Muhammad is everything. He is the Apostle of Allah with authority based on prophethood as well as community leader and head of state, head of government. He became the leader of God's decree. As a leader sharing decisions is taken through deliberation, and if the decision is determined based on his personal instincts he always controls by divine revelation. The Qur'an is a perfect norm of life for mankind. In there are concepts about ethics, politics, economics, and society. There are a number of verses that contain instructions and guidelines in the life of society and the state, in terms of leadership and government.